2011
DOI: 10.1007/s11676-011-0177-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rainwater harvesting on herbage diversity and productivity in degraded Aravalli hills in western India

Abstract: Over-exploitation and rural growth have severely damaged native vegetations of Aravalli hills in Rajasthan, India. This study was conducted to evaluate the effects of different restoration practices (i.e., rainwater harvesting (RWH) and planting of tree seedlings) on improvement in soil water and nutrients and growth and biomass of herbaceous vegetation. Contour trench (CT), Gradonie (G), Box trench (BT), V-ditch (VD) and a control were imposed on 75 plots (each of 700 m 2 ) in natural slope gradient defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
3
8
0
3
Order By: Relevance
“…Moreover, lower biomass production and percentage cover of perennial grasses in the degraded area could be a result of year round grazing which could not allow quick vegetation recovery in the study area (Verdoodt et al 2010). These findings corroborates with those of Singh et al (2011) who reported higher biomass production and percent cover in areas rehabilitated through rainwater harvesting. Similarly, Monsour et al (2013) found a higher percentage cover and biomass production in areas rehabilitated with stone terraces compared to unterraced ones.…”
Section: Herbaceous Biomass Production and Percentage Ground Coversupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, lower biomass production and percentage cover of perennial grasses in the degraded area could be a result of year round grazing which could not allow quick vegetation recovery in the study area (Verdoodt et al 2010). These findings corroborates with those of Singh et al (2011) who reported higher biomass production and percent cover in areas rehabilitated through rainwater harvesting. Similarly, Monsour et al (2013) found a higher percentage cover and biomass production in areas rehabilitated with stone terraces compared to unterraced ones.…”
Section: Herbaceous Biomass Production and Percentage Ground Coversupporting
confidence: 91%
“…This is in agreement with previous studies which have indicated that vegetation growth is directly related with phosphorus, soil organic carbon, potassium, and total nitrogen (Marcuzzo et al 2013). Singh et al (2011) in his study on Aravalli hills in western India found higher herbaceous biomass production and percent cover on lower slopes than in upper slopes.…”
Section: Herbaceous Biomass Production and Percentage Ground Covermentioning
confidence: 90%
See 3 more Smart Citations